Analysis and Design Procedure of Corner Gusset Plate Connection in BRBFs - Naghipour, M. (Iranica journal of energy & environment, 2013)
In order to achieve the post buckling strength of BRB member, AISC seismic design provisionsrequire that gusset plate axial capacity exceed ultimate compressive load of the BRB. The AISC code alsorequires that the gusset plate instability be considered because recent full scale tests demonstrated that outof plane buckling of a gusset plate occurs prior to BRB ultimate load. In this paper an analytical investigationis used to investigate inelastic compressive behavior and strength of gusset plates in BRBFs by finite elementsoftware considering plates of different dimensions. In order to verify analytical results one full scale tests wascarried out on a simplified gusset plate connection. Also to increase gusset plate buckling strength and improveits energy absorption behavior, effects of adding free edge stiffeners at different sizes have been investigatedand the results are presented. Finally, a design method accompanied by some design charts for rectangular typegusset plates subject to compression is proposed based on an inelastic plate buckling equation.